2011
DOI: 10.1089/jop.2010.0150
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Oxygen Saturation in Optic Nerve Head of Non-Human Primate Eyes Following the Intravitreal Injection of NCX 434, an Innovative Nitric Oxide-Donating Glucocorticoid

Abstract: Purpose: Hypoxia of the retina and optic nerve head (ONH) is believed to be pivotal in the development of ocular vascular disorders, including diabetic macular edema (DME). Glucocorticoids are among the most effective agents for the treatment of back of the eye diseases. However, this class of compounds is highly liable to increase intraocular pressure (IOP) and does not improve ocular perfusion or tissue oxygenation. Nitric oxide (NO) has vasodilating properties and lowers IOP in experimental models and human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…The compound has been shown to lack IOP raising effects, unlike TA alone, and to enhance oxygen saturation of the ONH in non-human primate eyes,13 suggesting potential retinal protective activity. We have now tested this hypothesis by comparing NCX 434 with TA on changes occurring in rabbit eyes exposed to retinal and ONH ischaemia/reperfusion caused by repeated injections of ET-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The compound has been shown to lack IOP raising effects, unlike TA alone, and to enhance oxygen saturation of the ONH in non-human primate eyes,13 suggesting potential retinal protective activity. We have now tested this hypothesis by comparing NCX 434 with TA on changes occurring in rabbit eyes exposed to retinal and ONH ischaemia/reperfusion caused by repeated injections of ET-1.…”
Section: Discussionmentioning
confidence: 99%
“…The glucocorticoid moiety is expected to provide ocular anti-inflammatory effects while NO is expected to have multiple additional effects: regulating intraocular pressure (IOP),10 promoting vasodilation in the eye11 and inhibiting proinflammatory cytokine via modulation of transcription factor nuclear factor kappa-B 12. Consistent with its dual mechanism of action, this compound has been shown to differentiate from TA in that it retains glucocorticoid binding affinity in recombinant human glucocorticoid receptors and enhances oxygen saturation in areas of the ONH of non-human primate eyes while not increasing IOP 13. Based on these and other observations, we hypothesise that NCX 434 could exert neuroprotective activities in pathological conditions where vasogenic alterations account for progressive retinal ganglion cell (RGC) loss, for example, in diabetic retinopathy 2…”
Section: Introductionmentioning
confidence: 99%
“…6,28 Retinal and optic nerve head oxygenation has also been shown to be increased by NO donor therapies in monkeys through vasodilation. 3 Additionally, the role of NO in anterior segment and TM physiology has been extensively evaluated.…”
Section: No Synthesis and Functionmentioning
confidence: 99%
“…76 It is possible that any ganglion cell and RNFL damage due to elevated IOP could be magnified due to the ability of anti-VEGF agents to negatively affect retinal and optic nerve head blood flow. 3 Horsley et al retrospectively investigated this concept and found that long-term anti-VEGF therapy did not result in RNFL loss. 78 This, however, was not corroborated by Martinez-de-la-casa et al They conducted a prospective investigation and determined that long-term anti-VEGF therapy resulted in a statistically significant decrease in RNFL thickness from baseline.…”
Section: Further Clinical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation